(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis explores the intertextual approach to analyzing literary texts, focusing on its theoretical foundations and application within Uzbek literature. Intertextuality reveals how texts interact with past literary traditions, cultural narratives, and ideological discourses. Through case studies of works by Abdulla Qodiriy, Erkin Vohidov, and Hamid Ismailov, the paper illustrates how Uzbek writers incorporate classical references and reframe historical narratives to engage with modern themes. The study underscores the dialogic nature of literature and the value of intertextual analysis in understanding textual depth, cultural continuity, and evolving literary identity in Uzbekistan.